Journal of Human Sport and Exercise - 2021 - Autumn Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc2.49
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of garlic and lemon extract combined with aerobic exercise on blood metabolic parameters and liver enzymes

Abstract: Purpose: The aim of this study was to evaluate the effects of aerobic exercise in combination with garlic and lemon on the lipid profile, metabolic parameters, and liver enzymes of obese male rats. Design: Sixty-four male Wistar rats were divided into eight equal groups consisting of 1) control following no treatment (n = 8); 2) hypercaloric fatty-food-based diet (n = 8); 3) aerobic exercise (AE, n = 8); 4) garlic intake (G, n = 8); 5) aerobic exercise with garlic intake (AEG, n = 8); 6) lemon intake (L, n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Previous studies have reported inconsistent results regarding the effects of AE and garlic consumption on LDL and cholesterol levels. Some studies have shown that AE and garlic consumption can improve these lipid profiles [21][22][23]. However, consistent with our findings, Bashiri et al (2015) did not find significant differences in LDL and cholesterol levels between exercise and garlic consumption groups compared to a control group [24].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have reported inconsistent results regarding the effects of AE and garlic consumption on LDL and cholesterol levels. Some studies have shown that AE and garlic consumption can improve these lipid profiles [21][22][23]. However, consistent with our findings, Bashiri et al (2015) did not find significant differences in LDL and cholesterol levels between exercise and garlic consumption groups compared to a control group [24].…”
Section: Discussionsupporting
confidence: 89%